Potential number of tooth losses in clicking, popping and crepitation of Temporomandibular Disorders (TMD) in elderly - Elfrida M. Agustina; Zahreni Hamzah; Zainul Cholid (DiscoverSys Inc., 2020)
Objective: Clicking, popping, and crepitation is the most common symptom of Temporomandibular Disorders (TMD). TMD can be caused by tooth loss, and tooth loss is widespread among the elderly. Material and Methods: This research is using a correlational analysis with a cross-sectional study approach. Tooth loss was divided into six regions (R1, R2, R3, R4, R5, R6) and joint sounds were divided into four categories (clicking, popping, crepitation, normal). Result: Multinomial logistic regression analysis test for overall tooth loss showed a p-value of 0.000 in clicking and crepitation, and for popping, it has a p-value of 0.248. The results of tests on six regions of tooth loss obtained a p-value of 0.017 at R1 for clicking sound and p-value of 0.014 at R2 for crepitation. This showed that clicking and crepitation had a significant correlation with the amount of tooth loss (p<0.05). Conclusion: The amount of tooth loss has a significant relationship with clicking and crepitation of Temporomandibular Joint (TMJ).